Effectiveness of Specific Prevention of Tick-Borne Encephalitis - M. S. Shcherbinina (Биопрепараты: Профилактика, диагностика, лечение, 2020)
Vaccination remains the only way to prevent tick-borne encephalitis (TBE). All TBE vaccines are based on strains of the Far Eastern and European subtypes of TBE virus. Currently, the Siberian subtype of the virus, which differs from the vaccine strains, accounts for 80–100% of the genetic population of TBE virus in most of Russia. The proportion of TBE vaccinated patients among those infected was different from year to year in Russia, e.g. 3.9% in 2012 and 1.5% in 2018, there were also some fatal cases registered among vaccinated patients. In this regard, evaluation of the effectiveness of vaccination against various genetic subtypes of TBE is a promising area of research. The purpose of this study was to summarise the results of studies investigating effectiveness of specific prevention of TBE as regards various genetic subtypes of the virus. The paper analyses data on the effectiveness of TBE vaccination in experimental settings and in real life. It was demonstrated that the use of vaccines for prevention of TBE is effective, provided the vaccination coverage is not less than 80%. The paper cites the data from a long-term study of the stability and protective activity of vaccine immunity against TBE virus strains isolated in highly endemic territories. It was established that TBE vaccines have high immunogenic activity and contribute to the production of stable protective antibodies against the strains of the three genetic subtypes of the virus. Protective efficacy of vaccination depends on the number of vaccinations received, the vaccination scheme, gender and age of those vaccinated. The paper concludes by saying that further studies are needed to assess TBE vaccine efficacy in order to improve vaccination tactics, to better understand causes of morbidity and mortality among vaccinated individuals.